USULAN PERBAIKAN KUALITAS PELAYANAN MODJOK KOPI CAFE MENGGUNAKAN METODE QUALITY FUNCTION DEPLOYMENT (QFD) - Sholih, Farrel Dwi Aprilla; Desrianty, Arie (e-Proceeding FTI, 2024)
Modjok Kopi Cafe is a cafe that sells drinks, heavy meals, and snacks. There are problems, namely income and the number of customers, which are still fluctuating towards a decline in the last 6 months, as well as complaints from customers. Modjok Kopi Cafe has made improvements but has not achieved significant results in terms of revenue and number of customers, so it is necessary to improve service quality. This research aims to determine service quality attributes that need to be improved using the gap analysis method at gap stage 5 and then determine technical specification priorities for carrying out corrective actions using the Quality Function Deployment (QFD) method. Based on the results of gap 5 data processing, there are 11 out of 21 attributes that get a negative gap or gap value (dissatisfied), which is used as a customer needs variable. There are 16 corrective actions in the technical specifications, which are priority improvements that need to be carried out first. There are 3 main priorities for corrective action, including: selecting the quality of food ingredients used in accordance with the Cost of Goods Sold (HPP); there is a Standard Operating Procedure (SOP) document for chefs in cooking that contains the food ingredients to be used, the composition of food ingredients and methods (techniques) of cooking; and innovating new submenu based on existing menus and adding new menus. Keywords: Customer Needs, Technical Specifications, Gap Analysis, House of Quality, and Quality Function Deployment ABSTRAK Modjok Kopi Cafe merupakan cafe yang menjual minuman, makanan berat serta snack. Terdapat permasalahan yaitu pendapatan dan jumlah pelanggan yang masih fluktuatif ke arah penurunan dalam 6 bulan terakhir serta adanya keluhan dari pelanggan. Modjok Kopi Cafe sudah melakukan usaha perbaikan akan tetapi belum mendapatkan hasil yang signifikan terhadap pendapatan dan jumlah pelanggan sehingga perlu dilakukan perbaikan kualitas pelayanan. Penelitian ini bertujuan untuk menentukan atribut atribut kulitas pelayanan yang perlu ditingkatkan menggunakan metode gap analysis pada tahap gap 5 kemudian menentukan prioritas spesifikasi teknis untuk melakukan tindakan perbaikan menggunakan metode Quality Function Deployment (QFD). Berdasarkan hasil dari pengolahan data gap 5 terdapat 11 dari 21 atribut yang mendapatkan nilai gap atau kesenjangan negatif (tidak puas) yang digunakan sebagai variabel customer needs. Terdapat 16 tindakan perbaikan dalam spesifikasi teknis yang menjadi prioritas perbaikan yang perlu dilakukan terlebih dahulu. Terdapat 3 prioritas utama tindakan perbaikan, diantaranya: pemilihan kualitas bahan makanan yang digunakan sesuai dengan Harga Pokok Penjualan (HPP); terdapat dokumen Standar Operasional Prosedur (SOP) untuk chef dalam memasak yang berisikan bahan makanan yang akan digunakan, komposisi bahan makanan serta cara (teknik) memasak; dan melakukan inovasi sub menu baru berdasarkan menu yang sudah ada serta menambahkan menu baru. Kata kunci: Customer Needs, Spesifikasi Teknis, Gap Analysis, House of Quality, dan Quality Function Deployment